MECHANISMS FOR ACTIVATING EMPLOYER ENGAGEMENT IN THE DEVELOPMENT OF PROFESSIONAL STANDARDS: A STRATEGIC FRAMEWORK FOR DEMAND-LED VOCATIONAL EDUCATION - Sharofaddinov Shihnazar Anvarovich (Web of Journals Publishing, 2026)
The alignment of vocational education outcomes with labor market requirements is the central challenge of modern human capital development policies. Professional standards serve as the fundamental “genetic code” of this alignment, translating abstract industry needs into concrete educational outcomes.
Keywords: Professional Standards, Employer Engagement, Vocational Education and Training (VET), Skills Mismatch, Institutional Theory, Labor Market Intelligence, National Qualifications Framework (NQF).